The Role of Denitrification on Arsenite Oxidation and Arsenic Mobility in an Anoxic Sediment Column Model with Activated Alumina - Sun, Wenjie (Biotechnol Bioeng, 2010)
Arsenite (As(III)) is the predominant arsenic (As) species in reducing environments. As(III) is less strongly adsorbed than As(V) at circumneutral pH conditions by common non-iron metal oxides in sediments such as those of aluminum. Therefore, oxidation of As(III) to As(V) could contribute to an improved immobilization of As and thus help mitigate As contamination in groundwater. Microbial oxidation of As(III) is known to readily under aerobic conditions, however, the dissolved oxygen (O(2)) concentration in groundwater may be limited due to the poor solubility of O(2) and its high chemical reactivity with reduced compounds. Nitrate (NO(3)(−)), can be considered as an alternative electron acceptor, which can support oxidation of As(III) to As(V) by denitrifying bacteria. In this study, two up-flow sediment columns packed with activated alumina (AA) were utilized to demonstrate the role of denitrification on the oxidation of As(III) to As(V) and its contribution to improved As adsorption onto AA. One column was supplied with NO(3)(−) (C1) and its performance was compared with a control column lacking NO(3)(−) (C2). During most of the operation when the pH was in the circumneutral range (d 50–250), the release of arsenic was greater from C2 compared to C1. The effluent As concentrations started increasing on d 60 and d 100 in C2 and C1, respectively. Complete breakthrough started on d 200 in C2; whereas in C1, complete breakthrough was never achieved. The effluent and solid phase As speciation was dominated by As(V) in C1, indicating the occurrence of As(III) oxidation due to NO(3)(−); whereas in C2, only As(III) was dominant. This study illustrates a bioremediation or natural attenuation process based on anoxic microbial NO(3)(−)-dependent oxidation of As(III) to more readily adsorbed As(V) as a means to enhance the immobilization of As on alumina oxide particles in subsurface environments.